(untitled) (Global Journal of Science Frontier Research, 2020)
Ferrite is soft-iron material and therefore it cannot be magnetized. However, the rings, made from ferrite, can be magnetized in the assigned direction. This special feature of the magnetization of such rings did not have, until now, of physical substantiation. In the article are examined the processes of the magnetization of the models of different configuration, including annular. It is shown that the magnetization of ferrite rings can be considered as the forced crystallization of magnetic moments.